Owners’ Portfolio Diversification and Firm Investment - Lyandres, Evgeny; Marchica, Maria-Teresa; Michaely, Roni; Mura, Roberto (Review of Financial Studies, 2019)
[Portfolio diversification of firms’ controlling owners influences their firms’ capital investment. Empirically, the effect of owners’ portfolio diversification on their firms’ investment levels is positive for publicly traded firms and tends to be negative for privately held ones. These findings are consistent with predictions of a model in which a risk-averse investor simultaneously chooses her portfolio structure, and both the level and riskiness of capital investment of the firm she controls, and in which the firm can be potentially constrained in its capital investment choices. Overall, our results indicate that owners’ portfolio underdiversification and firms’ financial constraints can affect firms’ resource allocation.]